TRANSITIONAL CARE FOR PATIENTS WITH CONGESTIVE HEART FAILURE AND CHRONIC LUNG DISEASE. (16th November 2018) - Koufacos, N; Ramirez, D; Hung, W; Boockvar, K
Abstract: To improve transitional care for patients with CHF and COPD, a collaboration was formed between the RN Care Coordinator and the GRECC Care Transitions Coordinator. This collaborative model was initiated to identify patients at risk for rehospitalization and to deliver a transitional care intervention. In January 2017, the project began. The team consists of one RN and one SW. The RN Care Coordinator reviewed the inpatient roster for 2 med/surgical units daily. Veterans admitted with a primary diagnosis of CHF and/or COPD were assessed while inpatient and those who were age 60 years or older and were deemed appropriate for care transitions based upon established criteria were referred to the SW for care transitions. Enrolled Veterans received post discharge support consisting of face-to-face visits, check in phone calls, and referrals for community resources. Fiscal year 2015 served as baseline data. Data from fiscal year 2018 compared with the baseline showed the ratio of observed vs. expected admission rating for patients with CHF decreased from 1.59 to 0.89 (1.0 as the reference rating and lower is better). The national ranking for readmissions due to CHF changed from 138 out of 140 hospitals to 38 out of 140 hospitals (lower is better). In a 12-month period the number of Veterans admitted to the hospital with CHF as their primary diagnosis moved from 196 to 96. These data demonstrate that RN Care Coordination and SW collaboration may be helpful in reducing readmissions for high risk patients with CHF and/or COPD.